Condicionantes Naturais e Socioecônomicos da Desertificação nos Trechos Médio e Baixo do Vale do Rio Jaguaribe no Estado do Ceará. - Muniz, Ana Cristina Fernandes (2009)
The desertification process constitutes itself in a form of degradation that became one of the serious environmental problems faced by Humanity. The areas that were susceptible to degradation/desertification were recognized by the Convention of Combated a Desertification (Desertification Combat Convention (1977) and were considered as such, those situated in the regions of arid, semi-arid and subhumid climate. The state of Ceará has most of the proportional area susceptible to desertification in the Brazilian Northeast with a preeminence of the areas of Irauçuba, Inhamuns and midstream, lower stream of Jaguaribe river. This study considered seven municipalities that were located along the Vale of Jaguaribe in its mid and lower stream, the municipalities chosen were: Alto Santo, Iracema, Jaguaretama, Jaguaribara, Jaguaribe, São João do Jaguaribe and Solonópole. The general objective of this research was to identify the conditioners of natural and socio-economical aspects of the process of desertification in this region, taking into account the characterization of environmental framework, observing its main potentialities (natural and socioeconomically) through the evaluation of impacts originated by the system of land use and evaluating the implication between the process of susceptibility to desertification and its impact over the socioeconomically characteristics of the area. The methodology used in the research had as its main fundamentation, the Beltrame focus (1994), that uses as its main parameter the standard analysis of vegetation through a comparison of satellite images betweens the years of 1986/89 and 2007. An application of the methodology allowed the realization of a general synthesis of the actual reality of the area regarding its problems, fragilities and potentialities of natural resources and socioeconomically aspects and to have a general vision of the degradation framework.